Modulation of lipid metabolism by exercise: exploring its potential as a therapeutic target in cancer endocrinology - Liu, Haodong; Yang, Tong; Choi, Seongbeom (Frontiers in Endocrinology, 2025)
Cancer progression is tightly linked to metabolic changes, particularly in lipid metabolism, which is crucial for tumor growth and metastasis. Exercise, known for its health benefits, is gaining recognition for its ability to influence cancer-related lipid metabolism. Metabolic shift prioritizes lipid oxidation over glucose metabolism, hence limiting the energy supply available to tumor cells and reducing their metabolic adaptability. Exercise also enhances mitochondrial function and aids the immune system, further bolstering its anti-cancer effects. Additionally, exercise mitigates cancer-related symptoms like fatigue, improves insulin sensitivity, and counteracts metabolic issues such as cachexia. Despite promising insights from studies, challenges persist in comprehending the molecular mechanisms of exercise’s impact on lipid metabolism in cancer. Future research should aim to identify optimal exercise regimens for cancer patients, explore the combined effects of exercise and cancer treatments, and delve into the molecular pathways connecting exercise with tumor suppression. With its potential benefits, exercise could act as a supportive therapy alongside conventional cancer treatments, enhancing patient outcomes and quality of life.